Minor alkaloids from an aqueous extract of the hook-bearing stem of Uncaria rhynchophylla. Issue 6 (3rd June 2021) - Li, Ruo-Fei; Zhu, Cheng-Gen; Xu, Cheng-Bo; Guo, Qing-Lan; Shi, Jian-Gong
Abstract: Seven new monoterpene alkaloids (1 −7 ), along with 18 known analogues, were isolated from an aqueous decoction of the hook-bearing stems of Uncaria rhynchophylla (Gou-teng). Their structures were determined by spectroscopic data analysis and electronic circular dichroism (ECD) calculations. Compound 1 is the first monoterpene 22-norindoloquinolizidine alkaloid with a ketene unit, while 2 and 3 are unusual indoloquinolizidine alkaloids having an oxazinane ring.